Fundos mútuos de investimento em ações no Brasil: incentivos, gestão e convergência - Silva, Ana Balbina Gomes (2011)
This article discusses the convergence patterns in time series of real accumulated return on a panel containing 68 stock mutual funds in Brazil, from January 1998 to June 2007, using the semiparametric methodology developed by Phillips and Sul (2007). In despite of the classical portfolio theory and the characteristics of this relevant market – high levels of regulation, transparency and informational efficiency and low transaction costs –, we can evidence a wide heterogeneous behavior, with four convergence clubs, which have transitional dynamics and very specific composition. A private financial institution as the manager, the incentives related to the lower administrative fees and performance fees and the relevance of riskadjusted return measured by different risk metrics are able to differ between a looser and a winner fund, influencing them to pursue an active strategies capable to “beat the market”. All these evidences are corroborated when in an aggregated analysis, where we construct equal-weighted portfolios formed using the funds of each club.